Plant adaptation and enhancement of phytochemicals in lettuce in response to environmental stresses - Oh, Myungmin (Kansas State University, 2008)
Studies were conducted to examine the role of antioxidants in adaptation of lettuce (Lactuca sativa L.) to unprotected environmental conditions and various environmental stresses. Antioxidants, in addition to being a plant defense mechanism, are phytochemicals that provide significant health-promoting and nutritive value in human diet. Various approaches involving mild environmental stresses and cultural and management practices have been used to enhance the quality of this commonly consumed leafy vegetable by improving its phytochemical and health-promoting attributes. Lettuce plants grown in protective environments adapt to unprotective environmental conditions by activating antioxidant genes such as phenylalanine ammonia-lyase (PAL), gamma-tocopherol methyl transferase (gamma-TMT), and L-galactose dehydrogenase (L-GalDH) involved in the biosynthesis of phenolic compounds,alpha-tocopherol and ascorbic acid, respectively. Mild environmental stresses such as heat shock, chilling, water stress and high light also activate these genes leading to the accumulation of secondary metabolites and phytochemicals without any adverse effect on biomass accumulation. The phytochemicals included chlorogenic acid, chicoric acid, caffeic acid, quercetin-3-O-glucoside and luteolin-7-O-glucoside. However, under field conditions, application of drought stress did not produce consistent results with regard to the phytochemical composition of lettuce. Plants grown in open field have higher phenolic content and higher antioxidant capacity than those grown in high tunnel. However, these plants also had less biomass accumulation. Many factors such as plant age, variety, fertilization, transplanting shock affected the phytochemical composition of lettuce. The red leaf variety 'Red Sails' had higher antioxidant capacity than 'Baronet' and younger plants had the highest phytochemical content. With regard to the management practices, there was no significant difference in phytochemical composition between organically and conventionally managed crops. Also, low fertility favored the accumulation of phytochemicals and increased the antioxidant capacity. Thus, the results show that mild environmental stresses along with appropriate cultural and management practices can enhance the quality of lettuce by improving their phytochemical composition.
Keywords: Lettuce; Phytochemicals; Environmental stresses; Antioxidants; Phenolics; Health; Agriculture, Food Science and Technology (0359); Agriculture, Plant Culture (0479); Biology, Plant Physiology (0817)